Effect of high hydrostatic pressure and reducing sodium chloride and phosphate on physicochemical properties of beef gels. Issue 2 (3rd April 2019) - Maksimenko, Anastasiia; Kikuchi, Ryo; Tsutsuura, Satomi; Nishiumi, Tadayuki
ABSTRACT: The effect of high hydrostatic pressure (HHP) treatment (100–200 MPa, 10 min, 20°C) combined with sodium chloride and sodium phosphate on the physicochemical properties of beef gels was investigated. The water content, cooking losses, color, protein composition by SDS-PAGE analysis and texture parameters of beef gels were determined. The beef gels treated with high pressure at 150 MPa showed a synergistic effect in the increased water content and the decreased cooking losses compared with the unpressurized gels. The L*, a* and b* color values of beef gels were slightly decreased under HHP treatment at 100–200 MPa. In the SDS-PAGE analysis, the staining intensity of the α-actinin protein band was decreased in pressurized samples. The cohesiveness, adhesiveness, gel strength and modulus of elasticity were improved after HHP treatment. Application of high pressure treatment (150–200 MPa) before heat treatment would be beneficial for the manufacturing of low salt and/or low phosphate meat products for a healthy diet.